Review: The Mutilation of Mark's Gospel - Telford, William R. (The journal of theological studies, 2004)
The Mutilation of Mark's Gospel N. Clayton Croy Pp. 230 Nashville, TN Abingdon Press 2003 0 687 05293 9. Paper$20